Substitution of Diluent Solution in Semi-Quantitative Examination of C-Reactive Protein - Yuliana, Linda; Khairunisya, Siti; Novita, Iswiyanti (Tropical Health and Medical Research, 2026)
The C-Reactive Protein (CRP) test using the agglutination method is performed through qualitative and semi-quantitative examinations. However, the diluent solution required for the semi-quantitative stage is not provided in the CRP reagent kit. The absence of this solution requires the laboratory to find an alternative diluent in order for the test to be conducted properly. This study aims to compare the effectiveness of 0.9% NaCl solution from table salt and 0.9% NaCl infusion solution with PBS as a diluent in semi-quantitative CRP examination and to provide an alternative diluent that is cheaper and easier to obtain. The study was conducted in the Immunology Laboratory, Health Polytechnic of the Ministry of Health Banjarmasin, using a true experimental design with a post-test only control group. Experimental groups included 0.9% NaCl from table salt and 0.9% NaCl infusion solution, while the control group used PBS. Nine positive CRP serum samples were used. Friedman test results showed no significant difference between the three diluent types (significance value 0.607 > ? 0.05). It was concluded that 0.9% NaCl solution from infusion and table salt can be used as diluents for semi-quantitative CRP examination. Further research is recommended to test storage stability and application in similar tests, such as Anti-Streptolysin O and Rheumatoid Factor.